Regional and Global Science : Publications from Latin America and the Caribbean in the SciELO Citation Index and the Web of Science (2016)
ABSTRACT: We compare the visibility of Latin American and Caribbean (LAC) publications in the Core Collection indexes of the Web of Science (WoS) —Science Citation Index Expanded, Social Sciences Citation Index, and Arts & Humanities Citation Index—and the SciELO Citation Index (SciELO CI) which was integrated into the larger WoS platform in 2014. The purpose of this comparison is to contribute to our understanding of the communication of scientific knowledge produced in Latin America and the Caribbean, and to provide some reflections on the potential benefits of the articulation of regional indexing exercises into WoS for a better understanding of geographic and disciplinary contributions. How is the regional level of SciELO CI related to the global range of WoS? In WoS, LAC authors are integrated at the global level in international networks, while SciELO has provided a platform for interactions among LAC researchers. The articulation of SciELO into WoS may improve the international visibility of the regional journals, but at the cost of independent journal inclusion criteria.